Changes in bone mineral density of adolescent mothers during the 12-month postpartum period - Malpeli, Agustina (2010)
Objective: Bone mineral density (BMD) loss has been described in adult women in the 12-month postpartum period. However, little is known about the precise BMD pattern in adolescent mothers. The present study aimed to evaluate BMD in Argentinean adolescent mothers followed up during the 12-month postpartum period. Design: Analytical, prospective clinical trial. BMD and body composition were determined by dual-energy X-ray absorptiometry; bone mineral content (BMC) and BMD were measured in the lumbar spine (L2–L4), femoral neck (FN), femur trochanter (TR), total hip (TH) and total body. Changes in BMD and BMC were analysed using ANOVA for pairwise comparisons. Other comparisons were performed with the paired-sample t test and Wilcoxon test; Pearson’s correlation coefficient was used to analyse the relationship among continuous variables. Setting: La Plata, Argentina. Subjects: Adolescent mothers (n 35; 17 years old or less) were recruited within 15 d after delivery. Studies and follow-up were performed at 15 d and 3, 6 and 12 months postpartum. Results: BMD and BMC losses at 3 and 6 months and recovery at 12 months fitted a quadratic curve (ANOVA) at the three sites studied (FN, TH, TR), in total-body BMD (P=0·000) and BMC (P=0·038). At hip sites, BMD loss occurred at 3 months (FN, P=0·000; TR, P=0·000; TH, P=0·000) and 6 months (FN, P=0·000; TR, P=0·000; TH, P=0·000) compared with basal values. Percentage BMD loss immediately after delivery up to 6 months was about 5%. Conclusions: Adolescents showed significant BMD and BMC losses at 6 months postpartum, with an almost total recovery at 12 months in all sites studied.